PENGARUH BAHAN PENGENCER SARI KACANG KEDELAI (Glycine max) TERHADAP VIABILITAS DAN NEKROSIS SPERMATOZOA DOMBA SAPUDI - Immelda, Kicky Hanis; Susilowati, Suherni; Yudaniayanti, Ira Sari (Ovozoa: Journal of Animal Reproduction, 2019)
The purpose of  study  was  to find out the effect of different concentrations of  soya bean extractin sperm diluter, stored at 5°C toward sperm viability and necrosis. The semen was divided into four groups :  P0: 0.1 ml sapudi ram  + 1 ml of diluent yolk citrate, P1: sapudi ram  0.1 ml + 1 ml diluent  soybeans extract konsentration 5%,  P2: 0.1 ml sapudi ram  + 1 ml diluent soybeans extract konsentration 10%,  P3: 0.1 ml sheep semen + 1 ml diluent soybeans konsentration 15%. The result showed that the dose of  soya bean extract diluter konsentration of  15% could increase the viability percentage and could decrease the necrosis percentage of sperm.